Reversing Traditional Gender Roles: Narratives of Househusbands With Working Wives - Paredes, Kyle Russelle; Silvestre, Anajane Marie; Buna, Teresa (Journal of Interdisciplinary Perspectives, 2025)
This study explored the narratives of five househusbands from Cavite, Philippines, focusing on their preparations for the role and experiences in financial management, childrearing, household management, interpersonal relationships, and time management. Participants were selected based on specific criteria: having children, being full-time househusbands for more than two months, having working wives, and living in a nuclear family setup. Initially, these men were breadwinners with minimal involvement in household chores. However, financial difficulties, such as low income, unstable earnings, and job loss, led them to transition into full-time caregiving roles. As they adapted, they demonstrated resilience, dedication, and care for their families, learning to manage daily responsibilities efficiently. They developed personalized time management strategies, acquired new household skills, and overcame challenges disciplining their children while expressing love differently. Over time, their competence in household and caregiving tasks improved, creating a sense of fulfillment and happiness in their roles. Reflecting on their experiences, participants concluded that being a househusband does not diminish one’s masculinity. Instead, their journey highlights the importance of redefining traditional gender roles, breaking societal stereotypes, and embracing diverse family dynamics in a changing social landscape.